Development Strategy of Roro Kuning Waterfall Tourism Area in Nganjuk Regency Based on the Integration of Natural Potential and Local Culture - Yoga Pratama; Intan Kusumaningayu; Darmansjah Tjahja Prakasa (Kirana Publisher (KNPub), 2026)
Roro Kuning Waterfall, located in Bajulan Village, Loceret Subdistrict, Nganjuk Regency, is a nature-based tourism site containing both Wilis mountain landscape potential and the local cultural narrative of the Roro Kuning legend. Despite these combined strengths, visitor numbers remain low, reaching only 4,095 visitors during the third quarter of 2025, lagging 95.04% behind Jolotundo Tourism located in the same village. This study aims to formulate an area development strategy that integrates natural and cultural potential as a unified destination management framework. The method is descriptive-qualitative, involving field observation, interviews with the Nganjuk Tourism Office, policy document review, SWOT analysis, and carrying capacity analysis based on the 2021 Ministry of Tourism guidelines. Findings show that the area covers ±75,900 m² divided into three zones (gateway 23,800 m², core tourism 35,100 m², Selo Agung Park 17,000 m²) with an ideal capacity of 350 visitors per day. The development strategy is formulated through the